ANALISIS DETEKSI POTENSI KESULITAN KEUANGAN PADA BANK MUAMALAT INDONESIA DENGAN LOGIT MODEL PERIODE 2008-2017 - Tedi Rochendi (Institut Teknologi dan Bisnis Swadharma, 2020)
Banking is an intermediary institution that has the main task of collecting funds from the community and channeling it back to the community in the form of loans / financing. In carrying out its duties as a financial services intermediary, Islamic banking must be more careful because one of the objectives of financial institutions, especially banks, is to support economic fundamentals from the threat of crisis and maintain stability. At the time of the 1998 economic crisis, Bank Muamalat, which was the first bank in Indonesia to implement sharia principles in its implementation, also did not avoid financial difficulties that could lead to bankruptcy. In the past few years, Bank Muamalat Indonesia (BMI) showed a decline in performance reflected in its financial performance. In 2014 and 2015, Net Performing Finance (NPF) BMI showed a fairly high level of 6.55% and 7.11%. This has exceeded the safe threshold of 5%. This study was conducted to analyze the prediction of financial difficulties in BMI with a logit model where the dependent variable is a categorical bank condition. The independent variable used is a CAEL ratio